2001
DOI: 10.1210/jcem.86.2.7176
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Examination at the Age of 15 Months of Extremely Preterm Infants after Postnatal Estradiol and Progesterone Replacement

Abstract: A randomized controlled pilot study was performed with a sample of extremely preterm infants to evaluate the impact of postnatal estradiol and progesterone replacement on postnatal bone mineral accretion. Twenty-five of 30 infants in the pilot study survived, and of these, 24 infants were available for the follow-up examination at a median chronological age of 18.1 months (minimum-maximum, 17.0--20.6) corresponding to a corrected age of 14.8 months (minimum-maximum, 12.9--17.4). Somatic growth data and bone mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In a recently reported small trial by Trotter and colleagues, intravenous E 2 and progesterone treatment in preterm infants tended to decrease the incidence of BPD. Furthermore, their work to date suggests potential added benefits on bone mineralization, retinopathy of prematurity, and neurologic outcome (49)(50)(51), lending further credence to the concept of postnatal estrogen treatment. In our model there were also favorable impacts on hypotension and patent ductus arteriosus that are also key complications of prematurity.…”
Section: Discussionmentioning
confidence: 93%
“…In a recently reported small trial by Trotter and colleagues, intravenous E 2 and progesterone treatment in preterm infants tended to decrease the incidence of BPD. Furthermore, their work to date suggests potential added benefits on bone mineralization, retinopathy of prematurity, and neurologic outcome (49)(50)(51), lending further credence to the concept of postnatal estrogen treatment. In our model there were also favorable impacts on hypotension and patent ductus arteriosus that are also key complications of prematurity.…”
Section: Discussionmentioning
confidence: 93%
“…PR expression in midbrain and brainstem nuclei during fetal and neonatal development implicates progesterone in the normal development of these structures and in several neurodevelopmental disorders. Elucidating the steroid sensitivity of the developing brain also becomes clinically important as the use of progestins in the treatment of premature infants (Trotter et al, 1999(Trotter et al, , 2001Trotter and Pohlandt, 2000) and of pregnant women for the prevention of premature delivery (Meis et al, 2003;Meis and Aleman, 2004;Dodd et al, 2005;Spong et al, 2005) increases.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that ER-mediated E 2 plays an important role in normal retinal vascular development and ROP pathogenesis (35). Maternal E 2 levels during pregnancy may increase by ~100-fold (33,(35)(36)(37)(38)(39). Fetal E 2 levels increase with gestational age, with the E 2 concentration peaking between 33 and 36 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%